EFFECTIVENESS OF TAXPAYER IDENTIFICATION NUMBER PREPARATION SERVICES THROUGH THE E-REGISTRATION SYSTEM AT KPP PRATAMA SUKABUMI - Sulthan Alfauzan, Naufal; Amirulloh, M Rizal; Hegia Sampurna, Rizki (Devotion : Journal of Research and Community Service, 2023)
The tax revenue target from 2018-2020 continues to increase as well as the realization of tax revenue from year to year has increased even though tax revenue continues to increase, but this revenue has not reached the predetermined target, in achieving the tax target requires awareness from taxpayers and compliance taxpayers in fulfilling their obligations in paying taxes in accordance with applicable regulations. One of the causes of not achieving the tax revenue target is the low compliance of the taxpayers themselves. This study aims to determine the effectiveness of the service for making taxpayer identification numbers through the e-registration system at the Sukabumi Pratama Tax Service Office. In this study the research method used is a qualitative method with a descriptive approach. The inhibiting factor for submitting an NPWP through the e-registration application in the field is the lack of public awareness to apply for an NPWP, besides that there is a lack of public understanding of the use of the e-registration system in registering NPWP and also there are still network disturbances when accessing the e-registration application.